Socio-economic and geographic equity in maternal health services utilization in Ethiopia: a community-based cross-sectional study - Zewditu Denu; Atkure Defar; Lars Persson; Seblewengel Lemma; Della Berhanu; Theodros Getachew; Solomon Shiferaw; Amare Tariku; Tadesse Guadu; Meseret Zelalem; Girum Taye; Joanna Schellenberg; et al. (BMC Health Services Research)
Abstract Background Addressing disparities in reproductive, maternal, newborn, and child health services is crucial in achieving the Sustainable Development Goal of universal health coverage. The persistence of social and geographic disparities in maternal health service coverage and utilization poses significant challenges. Ensuring equity in health service access and utilization as part of universal health coverage requires evidence whether these inequities exist. This study aimed to measure socio-economic and geographic equity in coverage and effective coverage of both antenatal care and skilled birth attendance. Methods We conducted a secondary analysis of data collected from the Performance Monitoring for Action Ethiopia from 2019 to 2020, including 2714 postpartum women at around six weeks and service delivery point assessment data from 462 health facilities. We measured inequities in the utilization of four or more antenatal care visits and skilled birth attendance using equiplots and concentration index. Moran’s I, Getis-Ord Gi statistics and Kriging interpolations were employed to analyze geographic variations of maternal health service utilization. Results In this study, 40% (95%CI: 36, 45) utilized four or more ANC visits, and 12% (95%CI: 11, 14) received quality antenatal care. Over half (54%, 95%CI: 48, 59) of women utilized skilled birth attendance, but only 7% (95%CI: 4, 8) received quality delivery care. The absolute equity gap between the least poor and the poorest women was 43 percentage points for ANC visits and 65 percentage points for skilled birth attendance. A higher proportion of women in Central and Northern parts of Ethiopia had four or more ANC visits and utilized skilled birth attendance, while most parts of the Eastern part of the country and most areas in the South had low levels of utilization. Conclusion The coverage of four or more antenatal care visits and skilled birth attendance was low and inequitable, with the poorest women receiving fewer services. The coverage varied across different parts of the country. Interventions that target groups of women and geographic areas with low coverage of services are crucial for reaching the goal of universal health coverage.